The Capacities and Limitations of the Newspaper Column as a Tool for Creating the Image of Its Author - Barańska-Szmitko, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The aim of this paper is to verify the capacities and limitations of the newspaper column (understood as a genre) as a tool for creating the image of its author. In the paper, the distinguishing features of a column are first presented, and then a hypothesis is proposed for predicting which attributes of its author may be generated by the column’s features. This hypothesis is juxtaposed with the results of empirical research. The main task of this research was to read the texts of one of two Polish columnists – Krzysztof Varga and Szymon Hołownia – and subsequently answer questions indicating the authors’ attributes. This procedure made it possible to recreate the image of the text’s author. The results demonstrated the influence of the column’s distinguishing features on the image of its author inferred by readers.